Kinetics and Mechanism of Ligand Exchange of Cu(methionine)2 by Polyamines - Abdul, Moheman; Showkat, Ahmad Bhawani; Khwaja Salahuddin, Siddiqi (Oriental Scientific Publishing Company, 2022)
The kinetics of ligand substitution reaction of Cu(methionine)2 complex by polyamines has been followed conductometrically above pH 9.0 at 25o C. Millimolar solution of the Cu(NO3 ) 2 and methionine in 1:2 molar ratio in water shows increase in conductance with time. When a polyamine (en, dien and trien) is added to the complex, the conductance increases at a rapid rate due to substitution of methionine by polyamine leading to the formation of [Cu(polyamine)2 ]. It was observed that the exchange of methionine by polyamine proceeds in a first order process. Since the rate of the reaction varies with the size of polyamines they can be placed in the following, en>dien>trien. In acidic pH range the absorption spectrum varies negligibly. However, the concentration of methionine does not have any influence on the absorption spectra.